Liver metabolic activities of Pasundan cattle induced by irradiated chitosan - Andi Mushawwir; JOHAR ARIFIN; DARMAWAN DARWIS; TITA PUSPITASARI; DEWI SEKAR PENGERTENI; NUNUNG NURYANTHI; RONNIE PERMAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mushawwir A, Arifin J, Darwis D, Puspitasari T, Pengerteni DS, Nuryanthi N, Perman R. 2020. Liver metabolic activities of Pasundan cattle induced by irradiated chitosan. Biodiversitas 21: 5571-5578. A total of one hundred and twenty-five, 2-3 year old male Pasundan cattle were used as livestock samples during the three months of this research. They were selected from the local cattle breeding and development center in Ciamis. The animal samples were randomly allocated to 5 treatment groups. One group served as the control, or without irradiated chitosan, while the others were used as treatment in varying levels. Each treatment group involved five replicates with 25 Pasundan bulls per treatment i.e five Pasundan bulls per replication. Each group was provided with the following rations: C0 = Control group, without IC (0 ppm IC); C1 = 350 ppm Irradiated Chitosan (IC); C2 = 400 ppm IC; C3 = 450 ppm IC; and C4 = 500 ppm IC. Irradiated chitosan was obtained through the following steps: extraction, deacetylation, and irradiation of chitin using gamma rays. Five mL of blood samples were collected from each bull at the beginning of each month of this experiment, which totaled three months. The blood samples were sucked from the tail/coccygeal vein using a sterilized syringe and vacuum tube containing K3EDTA. The plasma was used to determine the concentration of parameters related to liver metabolism through an automatic biochemical analyzer Kenza 240TX model from Biolabo, using a commercial kit. Each procedure was followed based on the Biolabo kit (Franch) and Randox kit (UK). This study showed that IC reduces the activity of glycogenolysis and glycolysis, but is accompanied by improvements in the biochemical conditions of liver cells. This is a favorable condition for the metabolism of Pasundan bulls in order to enhance their growth and reproduction.